2011
DOI: 10.3390/ijerph8103889
|View full text |Cite
|
Sign up to set email alerts
|

Is Neurodegenerative Disease a Long-Latency Response to Early-Life Genotoxin Exposure?

Abstract: Western Pacific amyotrophic lateral sclerosis and parkinsonism-dementia complex, a disappearing neurodegenerative disease linked to use of the neurotoxic cycad plant for food and/or medicine, is intensively studied because the neuropathology (tauopathy) is similar to that of Alzheimer’s disease. Cycads contain neurotoxic and genotoxic principles, notably cycasin and methylazoxymethanol, the latter sharing chemical relations with nitrosamines, which are derived from nitrates and nitrites in preserved meats and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(76 citation statements)
references
References 129 publications
3
73
0
Order By: Relevance
“…It is known that methylamine in a reaction that is catalysed by semicarbazidesensitive amine oxidase is metabolised to yield formaldehyde, hydrogen peroxide and ammonium (Yu, 1990). Later on it has been shown that in rodents L-BMAA is taken up by brain tissue and is enzymatically metabolized to compounds with genotoxic properties including the carcinogen formaldehyde (Kisby et al, 1992;Kisby and Spencer, 2011). Moreover hydrogen peroxide formed in the reaction may be degraded by catalase and thereby reactive oxygen species are formed.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that methylamine in a reaction that is catalysed by semicarbazidesensitive amine oxidase is metabolised to yield formaldehyde, hydrogen peroxide and ammonium (Yu, 1990). Later on it has been shown that in rodents L-BMAA is taken up by brain tissue and is enzymatically metabolized to compounds with genotoxic properties including the carcinogen formaldehyde (Kisby et al, 1992;Kisby and Spencer, 2011). Moreover hydrogen peroxide formed in the reaction may be degraded by catalase and thereby reactive oxygen species are formed.…”
Section: Discussionmentioning
confidence: 99%
“…These diseases include the amyotrophic lateral sclerosis/parkinsonism dementia complex among the Guamanians; neurolathyrism among Europeans, Indians, and populations of the Horn of Africa; and tropical ataxic neuropathy or konzo among sub-Sahara Africans. 1,2 We focus on the molecular determinants of susceptibility to konzo, a poorly known self-limited and irreversible upper motor neuron disease (spastic paraparesis) highly prevalent in Congo-Kinshasa, Mozambique, Tanzania, Central African Republic, Angola, and Cameroon. The main clinical picture consists of a symmetrical, permanent, and irreversible spastic paraparesis with no signs of sensory or genitourinary impairments.…”
mentioning
confidence: 99%
“…In subsequent studies, BMAA was shown to be neurotoxic (e.g. [31,44]), and BMAA exposure is at present regarded as one of the possible causes of ALS/PDC on Guam [45].…”
Section: The Role Of Bmaa In the Aetiology Of Neurodegenerative Diseasesmentioning
confidence: 99%
“…However, the role of BMAA in the aetiology of ALS/PDC on Guam was heavily debated (e.g. [72,139,140]) and BMAA exposure is at present regarded as one of the possible causes of Western Pacific ALS-PDC [45].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation